Social security insurance model in Iran with a sustainable development approach: A comparative study of selected countries, Iran, Turkey and Denmark - Biglary Taleghani, Mohammad; Bagherzadeh, Mohammad Reza; Mehrara, Asadollah; Gholipour-Kanani, Yousef (Researcher Bulletin of Medical Sciences, 2021)
The social security system in any country is a mirror of the development and the level of welfare of that society, and sustainable development in any country has a direct relationship with the quantity and quality of social security services. Given the initial establishment of the social security system in almost all countries, as well as Iran, the main challenge in this area can be considered the development of quality, quantity and services in a way that is able to meet the needs of society. (Khaleghparast, Rasekh, Naimi, 2017). Therefore, this study intends to identify the gaps between the current situation and the desired situation, by presenting applications in the form of a proposed model, to design the desired social security system according to the characteristics and conditions prevailing in society and its final destination to determine the development process of the country. This study is a descriptive-comparative study and has been done in several stages. The findings indicate that there is a significant gap between the management, governance and establishment of the social security system in Iran and the sample countries, especially Denmark. In countries that have succeeded in establishing the social security system, they have paid special attention to the three indicators of development and empowerment (risk management and realization of prevention levels), macro-planning and how to provide services, and by recreating the position of government in the security system, as well as following the recommendations and patterns of communication by international organizations and institutions, which are always considered as policy theories, the reference of policy makers in this field, have achieved good success in creating social welfare and public satisfaction. In this regard, according to the information obtained, it seems that the Social Security Organization, in following the patterns, models and global systems in the field of social security, should undertake serious reforms in the field of macro planning, development and improvement of employees, as well as improving and developing service delivery, take effective steps towards achieving sustainable development of the country